2005
DOI: 10.1093/eurheartj/ehi581
|View full text |Cite
|
Sign up to set email alerts
|

Remodelling of the right ventricle after early pulmonary valve replacement in children with repaired tetralogy of Fallot: assessment by cardiovascular magnetic resonance

Abstract: Prompt RV remodelling, with reduction of RV volume and mass, is observed after performing PVR if the RV end-diastolic volume exceeds 150 mL/m(2). Early PVR may prevent the detrimental complications of severe pulmonary regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
159
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(170 citation statements)
references
References 28 publications
7
159
2
2
Order By: Relevance
“…Knirsch et al [6] determined pre-replacement RV end-diastolic volume as 201 ± 47 mL/m 2 , and RVEF as 45 ± 6%, while those values were found as 109 ± 15% and 42 ± 8%, 6 months after replacement. Although the studies in the literature found a statistically significant reduction in end-diastolic volume after replacement, they did not find any change in ejection fraction which reflected global systolic function [2,5,7,8]. In our study, although we found highly significant differences in end-diastolic and end-systolic volumes after replacement, we did not find any significant difference for ejection fraction (Table 1).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Knirsch et al [6] determined pre-replacement RV end-diastolic volume as 201 ± 47 mL/m 2 , and RVEF as 45 ± 6%, while those values were found as 109 ± 15% and 42 ± 8%, 6 months after replacement. Although the studies in the literature found a statistically significant reduction in end-diastolic volume after replacement, they did not find any change in ejection fraction which reflected global systolic function [2,5,7,8]. In our study, although we found highly significant differences in end-diastolic and end-systolic volumes after replacement, we did not find any significant difference for ejection fraction (Table 1).…”
Section: Discussioncontrasting
confidence: 80%
“…MRI has been indicated as the gold standard method to measure ejection fraction, and volumes and global systolic functions of both ventricles [2]. Reduced exercise capacity, which is a strong indicator of deterioration of the disease, is weakly correlated with RV performance capacity determined by MRI.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were subsequently confirmed by others. 12,14,23 In addition to volumes, CMR can also provide additional data on ejection fraction of both the RV and LV. In a cross-sectional study, Knauth et al 24 examined 88 patients with repaired TOF by CMR.…”
Section: Cardiac Magnetic Resonance Measurements As An Indication Formentioning
confidence: 99%
“…Several groups have recently used CMR to investigate the optimal RV size cutoff values for performance of pulmonary valve replacement [17,18]. We evaluated 22 young patients with severe pulmonary valve regurgitation and RV dilatation after TOF repair, and demonstrated that, if pulmonary valve replacement is performed when the RV enddiastolic volume is larger than 150 mL/m 2 , RV remodelling, i.e.…”
Section: Volume Overloadmentioning
confidence: 99%
“…We evaluated 22 young patients with severe pulmonary valve regurgitation and RV dilatation after TOF repair, and demonstrated that, if pulmonary valve replacement is performed when the RV enddiastolic volume is larger than 150 mL/m 2 , RV remodelling, i.e. a significant reduction of RV volume and mass, can be expected [17] ( fig. 3 and 4).…”
Section: Volume Overloadmentioning
confidence: 99%